Women at risk : domestic violence and women's health - Stark, Evan (Sage Publications, 1996)
Battering by men is the most significant cause of injury to women in our society. It is also a major cause of child abuse, murder, substance abuse and female suicide attempts. This volume, the result of 15 years of research conducted by the authors - a social worker and physician respectively - explores the theoretical perspectives of this dramatic expression of male domination, together with health consequences for women and clinical interventions. The authors found that the traditional resources women turn to for help reinforce male domination: the medical, psychiatric and behavioural problems presented by battered women arise because male strategies of coercion, isolation and control converge with discriminatory structures and institutional practices to make it extremely difficult, sometimes impossible, for women to escape from abusive relationships. Stark and Flitcraft argue for a political space to be opened up within families, communities and the economy - a space where male coercion is simply not tolerated.